Multilayer broadband absorbing structures for terahertz region. Issue 2 (21st December 2012) - Dubey, Ashish; Jain, A.; Jayalakshmi, C.G.; Shami, T. C.; Awari, N.; Prabhu, S. S.
Abstract In this research, electromagnetic waves absorbing multilayer composite structures have been developed for terahertz (THz) region. In the recent past, most of the efforts to absorb the THz radiations are based on metamaterials or multilayer coatings, which are narrowband and fragile in nature, respectively. Under this work, we have designed and developed multilayer composite structures for THz absorption. Magnetic materials based composite structure shows more than 99% absorption in 0.5–2 THz frequency region for both TE and TM polarizations. Mechanically stable composite structures with such broadband THz absorptivity have huge potential in aero sector for stealth applications. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:393–395, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27295